Increasing pullout strength of suture anchors in osteoporotic bone using augmentation—A cadaver study. Issue 3 (March 2015) - Braunstein, Volker; Ockert, Ben; Windolf, Markus; Sprecher, Christoph M.; Mutschler, Wolf; Imhoff, Andreas; Postl, Lukas Karl Leo; Biberthaler, Peter; Kirchhoff, Chlodwig
Abstract Background Rotator cuff tears are of increasing clinical impact in the physically active elderly patients. Recent research revealed, that a high percentage of these patients present with significant loss of bone mineral density at the insertion site of the rotator cuff, thereby compromising suture anchorage for operative repair. We therefore hypothesized that augmentation of suture anchors improves biomechanical properties in low bone quality. Methods 28 osteoporotic humeral heads were included in this biomechanical study. Bone quality at the anchor insertion sites (group 1: posterior–medial; group 2: anterior–lateral) within the greater tuberosity was analyzed using HR-pQCT (voxel size: 82 μm). Anchor positions of identical quality were then randomized to either conventional screw anchorage or polymethylmethacrylat augmented screw anchorage. All anchors were cyclically ramp-loaded until pullout. Findings Pullout strength accounted for 226 N in group I for conventional anchorage and for 332 N in augmented technique. In group 2 (anterior–lateral) the pullout strength was 209 N (conventional) and 304 N (augmented). Pull-out strength of augmented screw anchors was significantly higher in both groups (p < 0.05). Interpretation Compared to conventional insertion techniques, the cement augmentation technique increases the pullout strength of suture anchors in low bone quality significantly. Cement augmentation could therefore be a helpful tool for improved suture anchor stability, especially in locations of low bone quality.